Anti-GFAP-antibody positive postinfectious acute cerebellar ataxia and myoclonus after COVID-19: a case report. (December 2021) - Asan, Livia; Klebe, Stephan; Kleinschnitz, Christoph; Stettner, Mark; Köhrmann, Martin
We present a case of acute cerebellar ataxia and myoclonus with detected anti-GFAP-antibodies in a patient recently recovered from COVID-19. Main symptoms consisted of acute gait and limb ataxia and myoclonus. The patient improved considerably upon treatment with high-dose intravenous (IV) steroids. While cerebrospinal fluid (CSF) and magnetic resonance imaging (MRI) findings were unremarkable, anti-GFAP-antibodies were detected in the patient's serum and disappeared upon clinical remission at a 3-month follow-up. This case suggests that anti-GFAP-antibodies might be associated with some of the increasingly observed cases of postinfectious acute cerebellar ataxias in COVID-19 patients and aid in the diagnosis of this autoimmune complication. We recommend searching for these antibodies in serum and CSF in suspected cases. Early steroid treatment may prove beneficial for these patients.